دراسة واعادة تاهيل شارع الحرايق - صرصور, فداء; شويكي, محمد; شريف, ميس (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2012)
المشروع عبارة عن دراسة وتصميم شارع الحرايق(الواقع في منطقة الحرايق مقابل ضاحية الزيتون ) , وقد تم إختيار هذا المشروع لما له من أهمية حيوية , وعلى احتوائه للعديد من المشاكل والتي تتمثل بالتصميم الهندسي وعدم توفر التخطيط المناسب له من ممررات مشاه وبنية تحتية وتجمع مياه الأمطار وغيرها من عناصر التصميم الناقصة, حيث يشكل هذا المشروع تطبيقا للمفاهيم الهندسية والمواصفات الفنية الواجب إتباعها عند القيام بدراسة وتصميم أي طريق. إن الطريقة التي ستتبع في هذا المشروع سوف تعتمد على جانبين رئيسيان وهما العمل الميداني والعمل المكتبي ، ابتداء بالعمل الميداني الذي سيتم من خلاله عمل مضلع ( Traverse) يتم ربطه بالإحداثيات القطرية الفلسطينية وتصحيحه بشكل كامل ومن ثم عمل مخطط تفصيلي للشارع , واخذ مناسيب ومحطات على طول الشارع من اجل رسم المقاطع الطولية والعرضية له وما يتطلبه من أمور أخرى مثل تصميم التقاطعات والصرف الصحي وغيرها،كذلك التطرق لبعض الأمور الخاصة بالتصميم الإنشائي للطرق, أما العمل المكتبي فيتمثل بعمل التصميم والحسابات اللازمة لإتمام هذا المشروع, وذلك بالاعتماد على المواصفات العالمية للتصميم (AASHTO 2004) وعلى مجموعه من البرامج المساحية مثلAutodisk land ArcGIS, Civil3D,. The project is a study and design of road Beer-Saba`a (in the al-harayeq versus al-zayton district ), we are selected this project because of its importance in that region because it contains many problems and the lacks not matched the engineering of proper planning of its side walking, lighting and pedestrian, infrastructure and other design elements missing. This is where the project application of the concepts of engineering and technical specifications to be followed when doing the study and design of any road. The way to be followed in this project will depend on two main and two field work and office work, beginning with the field work that will be through the work of a Traverse is linked to coordinates national Palestinian and corrected fully and then served as an outline of the street, and took the levels and stations along the the road in order to draw sections of longitudinal and lateral is and what it requires from other things like the design of intersections, sanitation and other services, as well as to address some things for the design construction of ways, either office work be as follow, the work of design and calculations needed to complete this project by relying on a set of programs cadastral such as Auto disk land ArcGIS, Civil3D.
no of pages 113, 12701, 3/مساحة 2012 , in the store
Keywords: تأهيل الطرق